2022
DOI: 10.3390/cancers14205018
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Promoting the Efficacy of Chimeric Antigen Receptor T Cells in the Treatment of Hepatocellular Carcinoma

Abstract: HCC, one of the most common and deadly cancers worldwide, develops from hepatocytes and accounts for more than 90% of primary liver cancers. The current widely used treatment modalities are far from meeting the needs of liver cancer patients. CAR-T cell therapy, which has recently emerged, has shown promising efficacy in lymphoma and hematologic cancers, but there are still many challenges to overcome in its application to the clinical treatment of HCC, including osmotic barriers, the inhibition of hepatocellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…However, this approach often fails to promptly detect the off-tumor response or any adverse events associated with the therapy. Hence, as Table 2 shows, there is a pressing need in clinical practice for the observation of T cell growth, activation, and routine trafficking in order to assess the early stage of response and provide timely intervention [ 101 , 102 ].…”
Section: Monitoring the Efficacy Of Car-tmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach often fails to promptly detect the off-tumor response or any adverse events associated with the therapy. Hence, as Table 2 shows, there is a pressing need in clinical practice for the observation of T cell growth, activation, and routine trafficking in order to assess the early stage of response and provide timely intervention [ 101 , 102 ].…”
Section: Monitoring the Efficacy Of Car-tmentioning
confidence: 99%
“…Different transfection methods were created as a result of variable labeling efficiency of SPIO, including the combination with monoclonal antibody and the mixture of ferumoxytol, protamine, and heparin. Besides, it has been reported that other transfection methods such as electroporation, various transfection agents (e.g., poly-L-lysine, lipofectamine, and protamine sulfate), and conjugation of HIV-1 transactivator peptides may be toxic to cells, which could reduce the viability, phenotype, and efficacy of transfected cells [ 102 , 103 ]. Combined with biomaterials, researchers offered a different vision of better transfection.…”
Section: Monitoring the Efficacy Of Car-tmentioning
confidence: 99%
“… 79 Despite preclinical studies showing a certain activity of CAR-T therapy alone, its efficacy against solid tumors, including HCC, is still limited due to several obstacles such as the immunosuppressive tumor microenvironment in which PD-1 plays a relevant role. 75 This is particularly true in HCC where the GPC3-targeted CAR-T cells have been suggested to present a reduced cytotoxic effect in PD-L1 positive HCC mice models compared to PD-L1 negative mice, while GPC3-CAR-T cells carrying PD-1 blockade agents showed a significantly increased tumor suppression capacity compared to “classic” GPC3-CAR-T cells. 80 , 81 These data provide a rationale for combining CAR-T therapy with ICIs.…”
Section: Other Immune-based Strategiesmentioning
confidence: 99%
“…Glypican-3 (GPC3), NK group 2 member D (NKG2D) and CD147 represent potential targets for CAR-T in HCC of which GPC3 is probably the most studied. [75][76][77] GPC3 is a heparan sulfate proteoglycan playing an important role in cell proliferation and metastasis which is expressed in approximately 75% of HCC cells, but not in healthy liver tissue. 78 It has been demonstrated in HCC mice models that GPC3-targeted CAR-T cells induced perforin-and granzyme-mediated apoptosis in GPC3-positive HCC cells with also a reduction of Wnt signaling in cancer cells.…”
Section: Beyond Icismentioning
confidence: 99%
“…These antigens are now used for the development of several CAR-T cells, an adoptive T-cell transfer therapeutic strategy, to avoid the involvement of TCR [e.g., Clinical Trials.gov Identifier: NCT03198546 and NCT02395250]. However, mainly due to the specific immunological tolerance of the liver as the organ that filters the blood effluent from the intestine [ 3 ], the efficacy of CAR-T cells in HCC showed a low efficacy if compared to hematologic and lymphatic cancer, and needs to be improved [ 162 , 163 , 164 ]. In addition, serious toxicities such as immune effector-cell-associated neurotoxicity syndrome (ICANS) or even life-threatening immune-related toxicities, such as cytokine release syndrome (CRS), are not uncommon with the use of the CAR-T approach, requiring multidisciplinary management with the need to develop algorithms that can identify patients at high risk of toxicity [ 165 , 166 ].…”
Section: Nk and Nk-like T-cellsmentioning
confidence: 99%